Novel Research Models for Staphylococcus aureus Small Colony Variants (SCV) Development: Co-pathogenesis and Growth Rate - Lee, James; Zilm, Peter S.; Kidd, Stephen P. (Frontiers in Microbiology, 2020)
Staphylococcus aureus remains a great burden on the healthcare system. Despite prescribed treatments often seemingly to be successful, S. aureus can survive and cause a relapsing infection which cannot be cleared. These infections are in part due to quasi-dormant sub-population which is tolerant to antibiotics and able to evade the host immune response. These include Small Colony Variants (SCVs). Because SCVs readily revert to non-SCV cell types under laboratory conditions, the characterization of SCVs has been problematic. This mini-review covers the phenotypic and genetic changes in stable SCVs including the selection of SCVs by and interactions with other bacterial species.